PEMODELAN APLIKASI PEMBAYARAN PENDAFTARAN KURSUS PADA SANGER LEARNING BERBASIS WEBSITE MENGGUNAKAN UML - Muhammad Rofi Halmi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
Modeling the payment registration application for courses at Sanger Learning, based on a website using UML, is a research project aimed at developing a model or design for the course registration payment system at Sanger Learning that can be implemented using Unified Modeling Language (UML). UML is a visual modeling language used to design and develop information systems.